The First Case Report of X-Linked Sideroblastic Anemia With Ataxia of Chinese Origin and Literature Review - Xiong, Shiqiu; Jia, Yang; Li, Shijun; Huang, Peng; Xiong, Jie; Mao, Dingan; He, Qingnan; Liu, Liqun (Frontiers in Pediatrics, 2021)
X-linked sideroblastic anemia with ataxia (XLSA/A) is a rare X-liked inherited disease, which was linked to the ABCB7 gene mutations. So far, five families have been reported worldwide. We present the first Chinese family of XLSA/A with novel ABCB7 gene mutation (c.2024A > G) and make a retrospective literature review. All affected patients were male. Age of symptom onset was <2 years old. The main symptoms included ataxia, delay in motor development, and mild sideroblastic anemia with obviously increased erythrocyte protoporphyrin. In this case, he had new symptoms that had not been reported in other cases such as epilepsy and cryptorchidism. We also discuss the possible molecular mechanism linking ABCB7 gene mutations to sideroblastic anemia and ataxia.